Komplexe Fokussanierung in der Sepsis: extrakorporale Membranoxygenierung (ECMO) als Bridging-Konzept zur trachealen Fistelsanierung bei sepsisassoziiertem ARDS = Complex control of the source of infection in sepsis : extracorporeal membrane oxygenation (ECMO) as a bridging concept for tracheal fistula repair in sepsis-associated ARDS - Weiterer, Sebastian; Schmidt, Karsten; Deininger, Marlene; Ulrich, Alexis; Tochtermann, Ursula; Eberhardt, Ralf; Hofer, Stefan; Weigand, Markus A.; Brenner, Thorsten (Der Anaesthesist, 2016)
Here, we present a case of a tracheal fistula due to an anastomotic insufficiency following abdominothoracic esophageal resection. Despite immediate discontinuity resection, the tracheal fistula could not be surgically closed, resulting in incomplete control of the source of infection and an alternative treatment concept in the form of interventional fistula closure using a Y-tracheal stent. However, owing to existing severe acute respiratory distress syndrome (ARDS), which is associated with a considerable risk of peri-interventional hypoxia, a temporary bridging concept using venovenous extracorporeal membrane oxygenation (ECMO) was implemented successfully.